Neodymium isotope record and δ18O of sediment core SK221-05 from the South-East Arabian Sea - Lathika, N; Rahaman, Waliur; Tarique, Mohammed; Gandhi, Naveen; Kumar, Avinash; Thamban, Meloth (PANGAEA, 2019)
This study presents the first record of deep water mass circulation in the Arabian Sea based on authigenic Nd isotope record for the past 136 ka. The sediment core used for the study is SK 221-05 (9˚0'32'' N, 72˚5'32'' E, 2700 m water depth). Nd isotopes were measured in the authigenic fraction of the bulk sediments, as well as in planktic foraminifera shells from the selected depths. d18O isotope is also measured on planktic foraminifera Globigerinoides ruber for age calibration.
Keywords: d18O of planktic foraminifera; Neodymium isotope